Sylvia Plath’s October 1962 Poems: “Things Are Resolving” - Gary LEISING (E-REA)
This article examines the intertextual relationship between Plath’s letters and poems of October 1962. While a side-by-side reading of these texts allows for a richer biographical analysis of the poems, it also encourages readers to consider the process through which Plath transformed her life and daily thoughts into art. In the midst of her separation from husband Ted, Plath wrote many of her most well-known poems, including the bulk of the poems in Ariel. In addition, about twenty-five letters written during October appear in the second volume of The Letters of Sylvia Plath. In these poems and letters, we see conflicted speakers. Independence—personal and financial—and a view of better things to come suffuse many of the letters of this period while Ariel—especially as edited by Ted Hughes—appears darker, as does the ultimate and tragic trajectory of Plath’s biography. Yet reading these two months’ letters along with their poems and thinking about the order Plath left the Ariel manuscript in, we may see a tension between her writing and her life: While her life goes toward its dark close, her poems point toward rebirth and rejuvenation, as do some of her letters. Through a comparative reading of the letters and poems, we may better understand both the work and the life, particularly the various personae Plath crafts in each.